THE ROLE OF DIGITAL LITERACY AND DIGITAL INNOVATION IN IMPROVING THE PERFORMANCE OF STATE UNIVERSITIES WITH LEGAL ENTITIES (PTNBH) IN MALANG CITY - Muslim, Abd. Qadir; Suryadi, Suryadi; Setyono, Langgeng (Erudio Journal of Educational Innovation, 2023)
This study aims to explore the effect of digital literacy and digital innovation on the performance of State Universities with Legal Entities (PTNBH) in Malang City. This research is explanatory with a quantitative approach, using the survey method. The research population includes State Universities with Legal Entities (PTNBH) in Malang City, including Universitas Brawijaya and Universitas Negeri Malang. This population includes education staff and lecturers totaling 6231 respondents. Using the Finite Population Correction Factor (FPC) formula at a 5% significance level, 100 respondents were sampled. Data collection was done through questionnaires, and data analysis using path analysis with the smartpls application. The results of this study indicate that the implementation of digital literacy, digital innovation, and the performance of State Universities with Legal Entities (PTNBH) in Malang City has been going well. In particular, digital literacy does not have a significant influence on the performance of State Universities with Legal Entities (PTNBH), while digital innovation has a significant influence on the performance of State Universities with Legal Entities (PTNBH). In addition, digital innovation acts as a mediator between digital literacy and the performance of State Universities with Legal Entities (PTNBH) in Malang City.